PENGEMBANGAN KETERAMPILAN HIDUP (LIFE SKILLS) DI SD & IMPLIKASINYA DI PGSD - M. S. Sumantri (Perspektif Ilmu Pendidikan, 2007)
The growing problems in human life have changed the living value. The education institutions are expected to equip the student with life skills relevant to their daily problems. This article puts forward the importance of the life skills and discusses how the life skills should be developed for elementary school student. Further, the role of Elementary School Teacher Program (PGSD) in training and preparing the elementary school teacher candidates is also discussed.